Pukina possessive markers in Rituale seu manual Peruanum - Faucet Pareja, Carlos Alberto (2014)
The difficulties for a grammatical research of Pukina language based on its only textual vestige of relevance, the Rituale seu manuale Peruanum (Ore 1607), are exposed in this paper. The case for the grammatical status of Pukina possessive markers is used as an example. One of the conclusions is that Rituale’s pukina texts allow not only postulating two contrary assertions regarding the status of such markers, but also finding evidence for both of them.